Characteristics of HIV type 1 (HIV-1) glycoprotein 120 env sequences in mother-infant pairs infected with HIV-1 subtype CRF01_AE - Samleerat T. (2014)
We analyzed the characteristics of the envelope genes of human immunodeficiency virus type 1 in 17 mother-infant pairs infected with variants of the CRF01_AE clade. A total of 353 sequences covering almost the entire glycoprotein (gp) 120 region were available for analysis. We found that, even if the virus population in the mother was complex, only viruses of a restricted subset were transmitted to her infant, independently of whether transmission occurred in utero or during the intrapartum period. We did not find that shorter gp120 regions or fewer potential N-glycosylation sites (PNGS) were characteristic of viruses transmitted from mother to infant. However, our data suggest that a limited number of PNGS that seem to be conserved in all variants in infants but are not uniformly present in variants in mothers may confer an advantage for transmission of the virus, thereby high-lighting the potentially important role of the "glycan shield." This finding was particularly significant for the PNGS at positions N301 and N384. © 2008 by the Infectious Diseases Society of America. All rights reserved.